Investigation of the changes of biophysical/mechanical characteristics of differentiating preosteoblasts in vitro. Issue 1 (December 2015) - Subbiah, Ramesh; Suhaeri, Muhammad; Hwang, Mintai; Kim, Woojun; Park, Kwideok
Abstract Background Topography, stiffness, and composition of biomaterials play a crucial role in cell behaviors. In this study, we have investigated biochemical (gene markers), biophysical (roughness), and biomechanical (stiffness) changes during the osteogenic differentiation of preosteoblasts on gelatin matrices. Results Our results demonstrate that gelatin matrices offer a favorable microenvironment for preosteoblasts as determined by focal adhesion and filopodia formation. The osteogenic differentiation potential of preosteoblasts on gelatin matrices is confirmed by qualitative (Alizarin red, von kossa staining, immunofluorescence, and gene expression) and quantitative analyses (alkaline phosphatase activity and calcium content). The biomechanical and biophysical properties of differentiating preosteoblasts are analyzed using atomic force microscopy (AFM) and micro indentation. The results show sequential and significant increases in preosteoblasts roughness and stiffness during osteogenic differentiation, both of which are directly proportional to the progress of osteogenesis. Cell proliferation, height, and spreading area seem to have no direct correlation with differentiation; however, they may be indirectly related to osteogenesis. Conclusions The increased stiffness and roughness is attributed to the mineralized bone matrix and enhanced osteogenic extracellular matrix protein. This report indicates that biophysical and biomechanical aspects duringin vitro cellular/extracellular changes can be used as biomarkers for the analysis of cell differentiation.